Avaliação da genotoxicidade de compostos à base de agregado Trióxido Mineral (PRO ROOTMTA ®, MTA ANGELUS ® e PORTLAND CIMENTO ) em células somáticas de Drosophila Melanogaster - Vilarinho, Renata Hinhug (2004)
A large number of chemical agents including carcinogens and non-carcinogens have been tested for mutagenicity in Drosophila melanogaster. The study of mutagenicity is an important regulatory basis for clinically employed dental material that maintains direct contact with living tissue. The present work aimed to evaluate the genotoxic effect of different substances based on mineral trioxide aggregate (MTA) (ProRoot®, Angelus®) used as repair cement and sealant of communications between the inside and outside of the tooth; and Portland cement, used in construction. For this, the test for mutation detection and somatic recombination in D. melanogaster wing cells (SMART) was used. Two types of crosses were carried out: ST - standard (flr3 / TM3 females, BdS crossbred with mwh males) and high bioactivation - HB (ORR females; flr3 / TM3, BdS crossbred with mwh males). From both crossings are obtained descendants: labeled heterozygotes (MH) and balanced heterozygotes (BH). In the wings of MH individuals, mutant spots may originate either from mutations, deletions and recombinations, whereas in BH only mutational events lead to spot formation, since all recombinational events are eliminated. Larvae obtained from both crosses were treated indistinctly with different concentrations of MTA-based substances. As positive control, ethyl carbamate (urethane) (10.0 mM) was used and as negative control sterile distilled water. Emerging adult MH wings from both crosses were analyzed for mwh (multiple wing hairs) and flr (flare ') mutant spots. Spotting was performed by light microscope. Statistical analysis was performed using the conditional binomial test and the X2 test, with a significance level of p <0.05. Results showed a dose-dependent increase in the number of spots, with a positive result for simple small spots and total spots. These results allow us to suggest that, under the experimental conditions used, the MTA-based material is genotoxic, but with low mutagenic potential.